Pattern of rural library usage among rural youth in Malaysia - Samsuddin, Samsul Farid; Omar, Siti Zobidah; Bolong, Jusang; Alby, Jeffrey Lawrence D'Silva; Mohamed Shaffril, Hayrol Azril; Mazuki, Raidah (Medwell Journals, 2016)
This study aims to identify the pattern of rural library usage among rural youth in Malaysia. Data for the study were collected via questionnaires and based on a multi-stage cluster sampling, a total of 400 villagers from four districts in Malaysia was selected as the respondents. The analysis performed confirms that the majority of rural library visitors were mainly students and housewives and it was discovered that the internet services offered by the rural libraries were fully utilised by rural youth. Based on the results, it was be concluded that the rural library remains relevant to the rural communities for local development and could ensue as a centre for lifelong learning. It was the researcher’s hope that this study could assist the concerned parties in their decision making whether to upgrade or maintain the rural libraries for the purpose of future community development and continue to contribute to the local communities.